Pemanfaatan Kecerdasan Artifisial dalam Pendidikan Tinggi Swasta di Jakarta melalui Pendekatan Difusi - T. W., Alhidayatuddiniyah; Aliffia Teja Prasasty; Erika Agustiana; Suhendra (Edukasiana: Jurnal Inovasi Pendidikan, 2026)
Private universities in Jakarta face transformative pressures to manage innovation systematically amid intensifying educational competition and digital technology acceleration. This study aims to describe innovation management practices in Jakarta's private universities, analyze the innovation diffusion process through Rogers' theory, and map institutional positions on the S-curve of innovation diffusion. The study employs an integrative literature review approach, analyzing 32 journal articles from 2021-2025 through three-stage thematic analysis: open coding, axial coding, and narrative synthesis. Findings reveal that innovation management practices develop across three strategic domains: strengthening governance and entrepreneurship, digital transformation, and human resource capacity development. The majority of Jakarta's private universities are in the growth phase (early majority) of the S-curve, with innovation characteristics—relative advantage, compatibility, and observability—as primary adoption drivers, while technological complexity and resource constraints remain barriers. The study also identifies an "adoption leap" phenomenon in AI adoption contexts. This research enriches innovation diffusion theory with the concept of cumulative adoption readiness and provides strategic guidance for strengthening institutional innovation management in Jakarta's private universities.